Rheological Behaviour of ABS/Metal Composites with Improved Thermal Conductivity for Additive Manufacturing - Vicente F. Moritz; Harald Prévost; Janaína S. Crespo; Carlos A. Ferreira; Declan M. Devine (Designs, 2023)
Metal-reinforced polymer composites are suitable materials for applications requiring special thermal, electrical or magnetic properties. Three-dimensional printing technologies enable these materials to be quickly shaped in any design directly and without the need for expensive moulds. However, processing data correlating specific information on how the metal particles influence the rheological behaviour of such composites is lacking, which has a direct effect on the processability of these composites through melt processing additive manufacturing. This study reports the compounding and characterisation of ABS composites filled with aluminium and copper particulates. Experimental results demonstrated that the tensile modulus increased with the incorporation of metal particles; however, there was also an intense embrittling effect. Mechanical testing and rheological analysis indicated poor affinity between the fillers and matrix, and the volume fraction proved to be a crucial factor for complex viscosity, storage modulus and thermal conductivity. However, a promising set of properties was achieved, paving the way for polymer–metal composites with optimised processability, microstructure and properties in melt processing additive manufacturing.